The Public Engagement Industry: Distancing Publics through Managed Engagement and Ideologised Transparency - McLuskie, Ed (Javnost-The Public, 2023)
“Public Engagement” is a salient term that signifies industry-deployed strategies and tactics to manage public demands for recognition and participation in the formation of public policy. The term also includes government responses to these demands by outsourcing public-government relations to interested organisations. This Public Engagement Industry (PEI) legitimises actions and policies through consulting enterprises, public relations (PR) and commercial organisations that take advantage of weakened public spheres, to which the PEI contributes. The PEI is oriented toward officially planned outcomes by folding public concerns into formulaic engagement practices. A local example highlights generic lines of division between the PEI, its clients and resistance groups. More generally, the PEI's assumptions of communication, dialogue, deliberation, and transparency are criticised, along with its methods of data gathering that pose “public engagement” as though public stamps of approval had been demonstrated, claims that deserve critical analysis.